Trends in Black–White Employment Gaps Since the Great Recession. Issue 3 (September 2018) - Masterson, Thomas
The Great Recession had a devastating impact on labor force participation and employment. This impact was not unlike other recessions, except in size. The recovery, however, has been unusual not so much for its sluggishness but for the unusual pattern of recovery in employment by race. The Black employment–population rate has increased since bottoming out in 2010 while the White employment–population rate has remained flat. We examine trends in labor force participation and employment by race, sex, and age and determine that the explanation is a combination of an aging White population and an increase in labor force participation among younger Black people. We estimate the likelihood of labor force participation and employment among young men and women to control for confounding factors, such as changes in educational characteristics. We then decompose the gaps among groups and the changes over time in labor force participation using an Oaxaca–Blinder-like technique for nonlinear estimations. We find that much smaller negative impacts of characteristics and greater returns to characteristics among young Black men and women than among young White men and women explain the observed trends.